Isolated Perforation of Left Coronary Cusp after Blunt Chest Trauma. (23rd February 2015) - Maini, Rohit; Dadu, Razvan T.; Addison, Daniel; Cunningham, Luke; Hamzeh, Ihab; Wall, Matthew; Lakkis, Nasser; Tabbaa, Rashed
Abstract : Left coronary cusp perforation is an extremely rare consequence of blunt chest trauma. A 22-year-old male presented after a motor vehicle accident with dyspnea. Transthoracic echocardiogram (TTE) and transesophageal echocardiogram (TEE) showed moderate to severe aortic regurgitation with prolapsing right coronary cusp. In the operating room he was found to have a left coronary cusp tear near the annulus and an enlarged right cusp. The patient recovered well after successful aortic valve replacement with a mechanical valve. Traumatic aortic regurgitation with left cusp perforation is serious and surgical intervention may be lifesaving if performed timely.